An emerging trend in functional foods for the prevention of cardiovascular disease and diabetes: Marine algal polyphenols. Issue 8 (24th May 2018) - Murray, Margaret; Dordevic, Aimee L.; Ryan, Lisa; Bonham, Maxine P.
ABSTRACT: Marine macroalgae are gaining recognition among the scientific community as a significant source of functional food ingredients. Due to the harsh environments in which macroalgae survive, they produce unique bioactive compounds that are not found in terrestrial plants. Polyphenols are the predominant bioactive compound in brown algae and are accountable for the majority of its biological activity. Phlorotannins are a type of polyphenol that are unique to marine sources and have exhibited protective effects against hyperglycemia, hyperlipidemia, inflammation and oxidative stress, known risk factors for cardiovascular disease and diabetic complications, in cell culture, animal studies and some human studies. This review updates the information on marine polyphenols, with a particular focus on phlorotannins and their potential health benefits in relation to the prevention and treatment of risk factors for type 2 diabetes and cardiovascular diseases.